Central defects control of Ti-6Al-4V alloy with heavy section reduction during flat cross wedge rolling. Issue 1 (1st December 2022) - Shi, M J; Cheng, M; Zhang, S H; Tan, H; Chen, M; Petrenko, V; Kozhevnikova, G V
Abstract : Cross wedge rolling (CWR) process is expected as an efficient and innovative preforming process for the forged aero-engine blades. But it is still a grand challenge to control the process defects and the performance of the rolled parts. According to the requirements of an aero-engine Ti-6Al-4V (TC4) blade billet with heavy section reduction up to 83%, flat CWR tools were designed and optimized by the thermal-mechanical coupling finite element (FE) method. The metal flow, damage evolution, and the distribution of stress and strain during the forming process were analysed. Then, the CWR experiments were carried out on IM500 flat CWR mill under different technological conditions. The obtained rolled parts were subjected to non-destructive testing (NDT), tension tests and microstructure analysis. The results showed that the central defects, such as micropores and voids, which seriously reduce mechanical properties, occurred in some of the rolled parts more or less. The volume of central defects was closely related to the initial rolling temperature of the billets. When the heated temperature of the TC4 billet was higher than 850°C, the target rolled part without central defects can be obtained. This research work can be a reference for the single-wedge CWR forming of titanium alloy with heavy section reduction, promoting the application of CWR in the aero-engine blade preforming process.